Formulasi Dan Uji Sifat Fisik Sediaan Sabun Wajah Cair Ekstrak Biji Alpukat (Persea americana M) Dengan Variasi Natrium Lauril Sulfat Sebagai Surfaktan - Suci Damayanti; Nur Ermawati (Jurnal Medika Nusantara, 2023)
Avocado seeds have antibacterial activity. These antibacterials can be used to clean the skin. Then a formulation of a liquid facial soap was made from avocado seed extract. One of the ingredients that affect the physical properties of liquid facial soap is sodium lauryl sulfate as a surfactant. Sodium lauryl sulfate as a surfactant is known to have cleaning power and can produce a stable and qualified foam. . This study aims to determine the optimal concentration of sodium lauryl sulfate to produce a liquid facial soap that is stable and meets the requirements. This type of research is experimental. Avocado seeds are extracted by maceration method. Liquid facial soap was made into three formulas using varying concentrations of sodium lauryl sulfate FI (0.5%), FII (1.5%) and FIII (2.5%). The physical properties of liquid facial soap observed included organoleptic test, pH test, viscosity test, specific gravity test, foam height test, homogeneity test and skin irritation test in liquid facial soap. The results showed that the use of varying concentrations of sodium lauryl sulfate in FI, FII and FIII fulfilled the criteria for testing the physical properties of avocado seed extract liquid facial soap in the organoleptic test, pH test, viscosity test, specific gravity test, foam height test, homogeneity test and skin irritation test. Of all the formulas that met the criteria for sodium lauryl sulfate concentration, the most optimal formula was formula III (2.5%).